2015
DOI: 10.3892/ol.2015.3787
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic changes and nuclear factor-κB activation, but not microRNA-224, downregulate Raf-1 kinase inhibitor protein in triple-negative breast cancer SUM 159 cells

Abstract: Abstract. Raf-1 kinase inhibitor protein (RKIP) is a tumor suppressor and metastasis inhibitor, which enhances drug-induced apoptosis of cancer cells. Downregulation of RKIP may be significant in the biology of highly aggressive and drug-resistant tumors, for example triple-negative breast cancers (TNBCs). Potential causes for the low levels of RKIP expressed by SUM 159 TNBC cells were investigated in the present study. Bisulphite modification, methylation specific-polymerase chain reaction (PCR) and a TransAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 35 publications
1
25
0
3
Order By: Relevance
“…We had previously explained some possible molecular alteration in one cellular model of TNBC and showed that aberrant activation of NF-jB signaling is a frequent characteristic of TNBC (Labbozzetta et al, 2015). In this work, both Curcumin and DHMEQ again confirmed their inhibitory action on NF-jB activation and on expression of its important targets, like antiapoptotic factors, also in TNBCs (Notarbartolo et al, 2005;Poma et al, 2006).…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…We had previously explained some possible molecular alteration in one cellular model of TNBC and showed that aberrant activation of NF-jB signaling is a frequent characteristic of TNBC (Labbozzetta et al, 2015). In this work, both Curcumin and DHMEQ again confirmed their inhibitory action on NF-jB activation and on expression of its important targets, like antiapoptotic factors, also in TNBCs (Notarbartolo et al, 2005;Poma et al, 2006).…”
Section: Discussionsupporting
confidence: 67%
“…The assay was performed as described previously (Labbozzetta et al, 2015). Cell growth inhibition was expressed as a percentage of the absorbance measured in the control cells.…”
Section: Cell Growth Assaysmentioning
confidence: 99%
See 3 more Smart Citations